ANALISIS PELAKSANAAN INDEKS PENYAKIT RAWAT JALAN GUNA MENUNJANG EFEKTIVITAS PELAPORAN 10 BESAR PENYAKIT (RL 5.4) DI RUMAH SAKIT SALAK BOGOR - Mustachidah; Yuyun Yunengsih (Journal of Innovation Research and Knowledge, 2021)
Disease index is a summary arrangement of the list of disease types and sick conditions based on a classification system or numbering code as a means of communication. This outpatient disease index will be produced in the form of recapitulation of reports of the top 10 outpatient diseases, which are useful for hospitals and also as a report to the Health Office, District, Province and Ministry of Health. This reporting is used as a decision-making related to hospital management and management related top 10 diseases by the hospital and the Health Office. This research uses descriptive method with quantitative approach while data collection techniques used by the author is by means of observation techniques, interviews and library studies that have close relevance to the subject matter. From the results of the research that has been done, there are several problems, namely: 1) Diagnosis is incomplete and unclear, 2) The disease code is unclear or difficult to read, 3) Delay in the implementation of outpatient disease index. The suggestions provided are as follows: 1) The hospital gives a briefing for the writing of the diagnosis to the doctor and reminds the doctor to do a clear and complete recording, 2) The hospital provides a briefing for writing the disease code to the coder so that the disease code can be more clearly read and easy to understand. 3) The hospital conducts socialization, monitoring, evaluation routinely to the data processing department, treatment room and index so that the implementation of disease index can be carried out on time.